Prognosis of children who are carriers of hepatitis B. Issue 6566 (24th January 1987) - Wheeley, S M; Boxall, E H; Tarlow, M J
Abstract : Fifteen children who had become positive for hepatitis B surface antigen (HBsAg) by perinatal transmission were traced and re-examined after a mean of 8.1 years; all had been born in England to mothers from ethnic minorities who were carriers of HBsAg. Fourteen of the children remained carriers of HBsAg; of these, more girls than boys developed antibody to hepatitis B e antigen (anti-HBe). Those children whose transaminase activities had been above normal within the first three years of life were more likely to have developed anti-HBe. The earlier production of anti-HBe suggests that girls have a more effective immune response. Increased transaminase activity early in the course of asymptomatic carriage of HBsAg may be a favourable prognostic sign.